Near-infrared spectroscopy study for determination of adsorbed acetochlor in the organic and inorganic bentonites - Tomić, Zorica P; Ašanin, Darko; Đurović, Rada; Đorđević, Aleksandar; Makreski, Petre (Elsevier BV, 2012)
NIR spectroscopy is used to determine acetochlor herbicide adsorption on Na-montmorillonite (NaP) and organically modified montmorillonite (NaOM). Both montmorillonites NIR spectra shows bands at 7061 and 6791 cm(-1). Organo-montmorillonite is characterised by two emphasized bands at 5871 and 5667 cm(-1) that are attributed to the fundamental overtones of the mid-IR bands at 2916 and 2850 cm(-1). Bands at 6017 and 6013 cm(-1) are attributed to acetochlor adsorbed to organo-montmorillonite and Na-montmorillonite, which is confirmed by X-ray powder diffraction (XRPD). Greater quantity of acetochlor is adsorbed to organo-clays compared to non-modified montmorillonite. Acetochlor poses high risk to environmental contamination. Organo-clays are the most useful for removing acetochlor from water and soil.